Pengaruh Kompensasi dan Rekruitmen Terhadap Kepuasan Kerja Serta Dampaknya Pada Prestasi Kerja Guru SMK Nurul Falah Pekanbaru - Nazwar, Syauqi; Fitri, Kurniawaty; ', Machasin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This research was conducted at SMK Nurul Falah Pekanbaru. The purpose of this study to obtain valid and reliable information about: a) the effect of compensation on the performance of teachers of SMK Nurul Falah Pekanbaru, b) the effect on the performance of teachers recruitment SMK Nurul Falah Pekanbaru c) the effect of compensation on job satisfaction of vocational teachers Nurul Falah Pekanbaru, d) the effect of recruitment on job satisfaction of vocational teachers Nurul Falah Pekanbaru, e) the effect of job satisfaction on the performance of the vocational teacher Nurul Falah Pekanbaru. The results showed that a) There is a compensation effect on the performance of teachers of SMK Nurul Falah Pekanbaru, b) There is a recruitment effect on the performance of teachers of SMK Nurul Falah Pekanbaru, c) There is a compensation effect on job satisfaction of vocational teachers Nurul Falah Pekanbaru, d) influences of recruitment to job satisfaction of vocational teachers Nurul Falah Pekanbaru, e) There is the influence of job satisfaction on the performance of the vocational teacher Nurul Falah Pekanbaru.Keywords: Compensation, Recruitment, Job Satisfaction, Achievement.